Tier-2 methane emission factor for pregnant alpacas grazing cultivated pastures in the Peruvian Andes - Garcia, Edward; Gualdron-Duarte, L.B.; Gere, J.I.; Loza, C.; Garcia-Ticllacuri, R.; Huanca-Marca, N.; Velez-Marroquin, V.M.; Pinares-Patino, C.S. (International Livestock Research Institute, 2025)
Alpaca farming in the high-altitude Peruvian Andes is an indigenous livestock system, yet their greenhouse gas (GHG) contributions for inventory purposes remain underexplored. This study aimed to assess the impact of alpaca variety (Huacaya vs. Suri) and period (Transition vs. Wet) on the estimation of the Tier-2 emission factor (EFs; kg of CH4 head-1year-1) in late-gestation female alpacas grazed rotationally on cultivated pastures. This study was conducted in Cusco, Peru (13° 55' 1.9" S, 71° 37' 14.7" W) at 4,141 m.a.s.l. Eight Huacaya (56.9 ± 4.29 kg LW) and six Suri (59.4 ± 4.29 kg LW) adult females were kept on a cultivated mixed pasture dominated by perennial ryegrass (68%), legumes (lucerne and clovers) and herbs (plantain and chicory), constituting 16% each, respectively. The first period (26 days) took place in November 2021, at the end of the dry season (‘Transition’), with the females in their 8–9 months of gestation. Period 2 started in January 2022 (10–11 months of gestation), at the beginning of the rainy season (‘Wet’). Experimental paddocks were set up on rotational grazing (60 days resting period), and the area of grazing strips was adjusted to guarantee an ad-libitum daily herbage allowance. Dry matter intake (DMI; g d-1) was assessed via total faecal collection over five days and in vitro DM digestibility. Gross energy content (GE; MJ kg DM-1) of the consumed diet was estimated using an empirical equation from the chemical composition of the grazed herbage. Enteric CH4 emissions were measured using the sulphur hexafluoride (SF6) gas-tracer technique. Enteric Tier-2 EFs were computed from the GE intake (GEI) and the CH4 conversion factors (CH4/GEI; Ym, %), both obtained in this study, according to guidelines in the Intergovernmental Panel on Climate Change (IPCC). Data were analyzed using a repeated measures model, with alpaca variety and experimental period as fixed effects, and alpaca within variety as random. This study demonstrated that the experimental period (aligned with two late gestation stages) had a stronger influence than alpaca variety on feed intake and CH4 emissions. Tier-2 EF decreased from 11.7 to 8.61 kg of CH4 head-1year-1 from the Transition to the Wet period, respectively (P = 0.041). Average Tier-2 EF for the entire late-gestation (8–11 months) was estimated to be 10.2 ± 2.57 kg of CH4 head-1year-1. The last overestimated in 28 % the current IPCC fixed Tier-1 EF value for alpacas of 8.0 kg of CH4 head-1year-1 (liveweight = 65 kg). Discrepancies on EFs between estimated Tier-2 and Tier-1 values are indicative of the context of this study, and extrapolations should be taken with caution. One limitation is the short length of experimental periods. Also, the IPCC Tier-2 equation does not account for liveweight losses (as was observed in the transition period). Despite drawbacks, the utilization of Tier-2 EFs should be preferred and, in the future, improved (aiming for Tier-3 calculations). More studies under more real husbandry conditions (extensive) are required to help policymakers make better decisions towards enhancing the sustainability of traditional alpaca production. This underscores the need for developing EFs addressing specific production settings towards refining GHG inventories.